2016
DOI: 10.1186/s12890-016-0208-2
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of sputum and systemic inflammation in asthma phenotypes: are paucigranulocytic asthmatics really non-inflammatory?

Abstract: BackgroundThe technique of induced sputum has allowed to subdivide asthma patients into inflammatory phenotypes according to their level of granulocyte airway infiltration. There are very few studies which looked at detailed sputum and blood cell counts in a large cohort of asthmatics divided into inflammatory phenotypes. The purpose of this study was to analyze sputum cell counts, blood leukocytes and systemic inflammatory markers in these phenotypes, and investigate how those groups compared with healthy sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 32 publications
7
89
0
Order By: Relevance
“…Herr et al 89 also described wheezer phenotypes in very young children in a French birth cohort including a mild episodic viral wheeze, which was very similar to our EVW group. 91 93 poor disease prognosis is attached to particular severe phenotypes. This is also consistent with findings from Tucson where children with early transient wheeze were less likely than persistent wheezers to have frequent episodes of wheeze or wheeze apart from colds in infancy.…”
Section: Paucicellular Asthma Phenotypementioning
confidence: 99%
“…Herr et al 89 also described wheezer phenotypes in very young children in a French birth cohort including a mild episodic viral wheeze, which was very similar to our EVW group. 91 93 poor disease prognosis is attached to particular severe phenotypes. This is also consistent with findings from Tucson where children with early transient wheeze were less likely than persistent wheezers to have frequent episodes of wheeze or wheeze apart from colds in infancy.…”
Section: Paucicellular Asthma Phenotypementioning
confidence: 99%
“…Epithelial cells may also release thymic stromal BARCELONA RESPIRATORY NETWORK lymphopoietin (TSLP) and IL-33, which stimulate innate lymphoid cells to release cytokines like IL-5 46 . Whichever the type of lymphocyte involved in this immunological process, eosinophilic asthmatics display greater sputum lymphocyte and epithelial cell counts, supporting the concept of a close interaction between lymphocytes and eosinophils leading to epithelial injury and shedding 28 . What seems clear is that eosinophilic asthma appears to be determined by different molecular mechanisms and gene expression as compared to other asthma phenotypes.…”
Section: Mechanisms Leading To Airway Eosinophilia In Asthmamentioning
confidence: 63%
“…The IgE-mediated sensitisation to animal dander has recently been shown to be particularly associated with the eosinophilic phenotype. However, sputum eosinophilia may be present in asthma irrespective of the atopic status 28 . Though it has been shown that non-atopic asthmatics may sometimes have airway IgE production directed towards some aeroallergens 45 , there is currently great interest in epithelial cells and innate lymphoid cells as key players in driving eosinophilic inflammation in nonatopic subjects 46 .…”
Section: Mechanisms Leading To Airway Eosinophilia In Asthmamentioning
confidence: 99%
“…Several large cohort studies including more than 100 patients have reported the proportion of eosinophilic asthmatics. Though differences may appear between the studies based on the disease severity, treatment with inhaled corticosteroids (ICS), and the proportion of atopic patients in the different asthma cohorts, it is reasonable to conclude that eosinophilic asthma represents approximately half of the patients and that this figure is possibly increasing with disease severity 13,17,22,[27][28][29][30][31][32][33] (Table 1). There is more controversy regarding the neutrophilic threshold that defines a neutrophilic asthma phenotype.…”
Section: Taking Into Account Eosinophilic Inflammation In Diagnosis Omentioning
confidence: 99%
“…Thresholds ranging from 49 to 93% have been proposed by different research groups. What is well established is that neutrophil count, in contrast to eosinophil count, increases with age 34 and cumulative smoking history 28 . Our threshold value for sputum neutrophil counts based on large series of healthy subjects, whose mean age is around 40 years, is as high as 76%.…”
Section: Taking Into Account Eosinophilic Inflammation In Diagnosis Omentioning
confidence: 99%